2000
DOI: 10.4049/jimmunol.165.10.5884
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of CD95 Ligand-Induced Neutrophil Infiltration to the Bystander Effect in p53 Gene Therapy for Human Cancer

Abstract: Clinical trials of adenoviral p53 gene therapy provide the evidence that the bystander effect induced by the wild-type p53 gene transfer on adjacent tumor cells contributes to tumor progression; its mechanism, however, remains uncharacterized. We report in this work that injection of adenovirus expressing the human wild-type p53 gene (Ad5CMVp53) into established human colorectal tumors in nu/nu mice resulted in CD95 ligand (CD95L) overexpression, followed by a massive neutrophil infiltration. Culture supernata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Intratumoral injection of adenovirus expressing the wt-p53 gene had substantial therapeutic activity in animal models as well as in clinical trials (31,32); the effects, however, seem to be limited within the local areas. Nikitina et al (33) reported that MethA tumor growth was significantly slowed by immunization of mice with Ad-mp53-transduced DCs (4 ϫ 10 5 and 2 ϫ 10 5 cells were injected i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral injection of adenovirus expressing the wt-p53 gene had substantial therapeutic activity in animal models as well as in clinical trials (31,32); the effects, however, seem to be limited within the local areas. Nikitina et al (33) reported that MethA tumor growth was significantly slowed by immunization of mice with Ad-mp53-transduced DCs (4 ϫ 10 5 and 2 ϫ 10 5 cells were injected i.v.…”
Section: Discussionmentioning
confidence: 99%
“…However a few reports present some interesting possibilities. Waku et al 44 have reported that intratumoral inoculations with Advp53, which causes an overexpression of CD95 ligand (Fas ligand ), induced antitumor effect through neutrophil infiltration into human colorectal xenograft tumors. They suggested that this neutrophil accumulation was responsible for a bystander apoptotic effect in nontransduced tumor cells.…”
mentioning
confidence: 99%
“…They suggested that this neutrophil accumulation was responsible for a bystander apoptotic effect in nontransduced tumor cells. 44 Nishizaki et al 45 also showed that recombinant Advp53 gene transfer into a mutant p53-expressing human nonsmall cell lung cancer cell line markedly inhibited the expression of an angiogenic factor, VEGF, and increased the expression of a novel antiangiogenic factor, brain -specific angiogenesis inhibitor 1 ( BAI -1 ), resulting in reduced tumor neovascularization in vivo. They attribute these results to a bystander effect leading to antiangiogenesis induced by the exogenous wtp53.…”
mentioning
confidence: 99%
“…36 This bystander effect probably involves the repression of neoangiogenesis through the down -regulation of vascular endothelial growth factor expression, 37 as well as immunomodulation through the enhancement of neutrophil infiltration through the overexpression of CD95 ligand. 38 In the present study, although after a single injection the transgene expression is transient and lasts no longer than 4 days, we showed that effective transgene expression can be maintained using nontoxic, iterative intratumoral transfection. In such conditions, tumor growth inhibition was found to last for 4 weeks, as long as the gene transfer was maintained.…”
mentioning
confidence: 85%